Thailand; the golden land - Edmonds, I. G (Indianapolis Bobbs-Merrill, 1972)
Traces Thailand's history and includes a brief look at its cultural, economic, and political scene today.
Bibliography: p. 165.
1
Keywords: Thailand -- History -- Juvenile literature